2016
DOI: 10.1016/j.gca.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Mercury transformation and release differs with depth and time in a contaminated riparian soil during simulated flooding

Abstract: Riparian soils are an important environment in the transport of mercury in rivers and wetlands, but the biogeochemical factors controlling mercury dynamics under transient redox conditions in these soils are not well understood. Mercury release and transformations in the O a and underlying A horizons of a contaminated riparian soil were characterized in microcosms and an intact soil core under saturation conditions. Pore water dynamics of total mercury (Hg T), methylmercury (MeHg), and dissolved gaseous mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 104 publications
(230 reference statements)
6
28
0
Order By: Relevance
“…This increase in THg concentrations is likely due to the lack of formation of biogenic sulfide. This observation is consistent with a previous study [37], in which aqueous concentrations of THg were observed to be highly variable in response to redox oscillations in a microcosm experiment containing riparian soils.…”
Section: Ph Redox Potential and Alkalinitysupporting
confidence: 93%
“…This increase in THg concentrations is likely due to the lack of formation of biogenic sulfide. This observation is consistent with a previous study [37], in which aqueous concentrations of THg were observed to be highly variable in response to redox oscillations in a microcosm experiment containing riparian soils.…”
Section: Ph Redox Potential and Alkalinitysupporting
confidence: 93%
“…Hg 0 oxidation is thought to be more important in situations where thiol binding site availability is high relative to low extracellular Hg concentration (Lin et al 2014b). Given the ubiquitous nature of thiols in bacterial membranes (Yu et al 2014), Hg 0 oxidation by anaerobes is likely widespread in environments such as waterlogged soils (Mazur et al 2015;Poulin et al 2016) and anoxic lake sediments (Bouffard and Amyot 2009) where Hg 0 can dominate Hg speciation. When considered alongside the growing evidence for anaerobic Hg II reduction, these findings show that anaerobes are poised to be key players in controlling MeHg production in anoxic systems by catalyzing a dynamic anaerobic redox cycle.…”
Section: Chemotrophic Mercury Oxidationmentioning
confidence: 99%
“…In general, Hg in soils and sediments is controlled by inorganic and organic interactions, since it has an affinity to Cl − , OH − , S 2− , and S-containing functional thiol groups in organic ligands [7][8][9]. Organic matter can both mobilize and immobilize Hg, depending on the prevailing soil pH, redox, and flooding conditions [10][11][12][13]. In addition, in well-oxygenated soils, Hg can be mobilized by the presence of high concentrations of Cl − ions [14] that act as a complexing agent, and conditions potentially found in areas with high usage of road deicing salts [15].…”
Section: Introductionmentioning
confidence: 99%